(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
The echinoid Parascutella gibbercula (de Serres, 1829) (Echinoidea: Clypeasteroida) is reported from the Mali Potok area of the Medvednica Mountain in Croatia. The fossil site is situated in mixed siliciclastics and biocalcarenites of late Badenian age. These echinoids are large extremely flat echinoids, informally known as sand dollars. The discovered echinoids are preserved in situ. The environment of deposition is defined as a shallow, coastal, high-energy environment for which these sea-urchins have developed characteristic morphological features. The strength and hydrodynamic stability of their shells enabled the post-mortal colonisation of the skeleton by epibenthic organisms, creating a robust, relatively stable substrate within otherwise mobile, unconsolidated sediments (secondary hardground). The Mali Potok echinoid assemblage has an unusual taxonomic composition for the Late Miocene of Croatia.